Development, geography, and economic theory - Krugman, Paul R. (MIT Press, 1995)
Paul Krugman argues that the unwillingness of mainstream economists to think about what they could not formalize led them to ignore ideas that turn out, in retrospect, to have been very good ones. Krugman examines the course of economic geograph and development theory to shed light on the nature of economic inquiry.